THE EFFECT OF PROFITABILITY ON STOCK PRICE WITH COMPANY SIZE AS A MODERING VARIABLE - hidayat, david mu'amar; Pertiwi, Tri Kartika (Perpustakaan dan Penerbitan Unismuh Makassar, 2021)
The purpose of this research is to test the effect of profitability on stock prices with the size of the company as a variable moderation. This study used a population of food and beverage companies listed on the IDX during the period 2015 - 2019. The profitability ratio used is the return on asset (ROA). This research is based on signaling theory. This research uses the method of consulting the T-test analysis and the F test. There are 14 companies as samples obtained using the purposive sampling method. The data collection method used is the study of data documentation which is secondary data. The approach used is a quantitative approach with multiple linear regression in conducting hypothesis tests using spss applications as a tool in hypothesis testing. Test results in this study showed profitability had a significant influence on stock prices, and profitability had a significant influence on stock prices moderated by firm size.